Buckling analysis of two-and three-layer delaminated beams with and without bridging - Parlapalli Madhusudhana Rao (2008)
Delamination has been a subject of concern in engineering applications of layer structures. Buckling of two and three layer beams with asymmetrically located delaminations is studied in terms of newly introduced nondimensionalized axial and bending stiffnesses. Effective- slenderness ratio (ESR), another nondimensionalized parameter is also introduced in the analysis. The close form solution can serve as a benchmark for other numerical schemes for these problems of delaminations. Further, bridging effects are considered to study the buckling analysis of two layer delaminated beams as an eigenvalue problem by using Rayleigh-Ritz energy method. Results show that bridging was found to be effective for the cases of shallow delamination with moderate length and for the deep and long delamination. The ESR is found to be a controlling parameter of the buckling behavior for delaminated beams with and without bridging. Finally, finite element analyses are performed and a good correlation is observed between the theoretical and numerical results.